The Effort To Improve Critical Thinking SKILLS In Physics Learning Through Project Based Learning Model - Halmaida, Halmaida; Mahzum, Elmi; Susanna, Susanna (Universitas Syiah Kuala, 2020)
Students critical thinking skill of class X MIA-1 in SMAN 2 Bukit is very low. There is the effort to improve critical thinking of students applying Project Based Learning model (PjBL). The purpose of this research is to determine whether there is an enhancement in students critical thinking skills using the Project Based Learning model. This research is Classroom Action Research which was carried out as many as III cycles. The subjects in this research were all students of Class X MIA-1 in SMAN 2 Bukit, consisted of 16 students. The instrument used to collect the data was tests including pre-test, post-test, teacher and student activity sheets, and observation sheets of learning management using Project Based Learning model. The results showed that students critical thinking skill when Project Based Learning model applied was better than the learning which was not using The Project Based Learning model. It happened because using Project Based Learning model, the students played a role actively as learning center were given an issue in the project then they were asked to solve it.